PERAN ARTIFICIAL INTELLIGENCE DALAM MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SMA PADA PEMBELAJARAN DARING: SYSTEMATIC LITERATURE REVIEW - Salsabila, Falah; Nandang Mustafa, Ade; Anriani, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study employed a Systematic Literature Review (SLR) to examine the role of Artificial Intelligence (AI) in supporting self-regulated learning (SRL) among senior high school students in online mathematics learning. Using the PRISMA 2020 guidelines, 45 initial articles were identified and screened into 16 empirical studies that met the inclusion criteria. The findings showed that AI technologies, such as adaptive learning systems, Intelligent Tutoring Systems (ITS), generative AI, and learning analytics, positively supported students’ SRL through personalized feedback, adaptive scaffolding, and real-time monitoring. AI also facilitated socially shared regulation of learning (SSRL) in collaborative online learning. However, excessive dependence on generative AI may reduce students’ learning autonomy if not supported by proper pedagogical supervision. Overall, AI has strong potential to support adaptive, collaborative, and student-centered online mathematics learning. These findings provide practical implications for mathematics teachers in Indonesia to integrate AI as a pedagogical support tool that encourages students’ learning independence and collaborative engagement.